FACTORS INVOLVED IN MICROPROPAGATION OF CHRYSANTHEMUM (CHRYSANTHEMUM MORIFOLIUM ) - Rasheed , Khetam; Yaseen, Suaad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Various concentrations of plant growth regulators added to MS (Murashige & Skoog) media were used to multiply chrysanthemum shoots. pH, sugar and licorice extract. Before being used as attest material, using the ex vitro obtained plant, a nodal piece was sterilized with 1.0% mercuric chloride (HgCl2) for five minutes.MS medium supplemented with BA at a lower concentration (1.0 mg.l-1) showed the best results when compared to other concentrations (8.7 shoots/explants, 7.5 cm, 17.1 leaves/explants and 4.0 nodes/explants)were studied. The average shoot length, nodes per explants, leaves per explants, and number of shoots per explants were all greater in the medium containing 30 g.l-1 sucrose, with values of 6.0 shoots per explants, 4.83 cm, 14.2 leaves per explants, and 3.6 nodes per explants, respectively Results showed that the effect of licorices extract gave the highest response percentage at concentration 50 ml.l-1 (13.5 shoots /explants, 8.5 node/explants, 3.5 leaves / explants and 4.82cm) respectively. It was shown that media with a pH adjustment of 5.7 produced the maximum nodes per shoot, leaves per shoot, average length of shoot, and number of shoots per explants (3.3 nodes per shoot, 14 leaves per shoot, 5.77 cm and 6 shoots per explants, respectively).Concerning the root formation stage, the concentration (0.1 mg.l-1) IBA with 1/4 MS salt strength gave the highest value for all parameters. While, the acclimatization stage showed the culture media supplemented with soil + Peat moss (1:1) gave the highest response percentage 100%. The best treatment was recorded at 1/2 MS salt strength with (2.5 mg.l-1) licorices extract for most characterize.